The Art of Living: John Dewey and the Melioristic Character of Aesthetic Experience - Luque-Moya, Gloria (My University, 2019)
Today aesthetics is a fertile branch of research which tries to transcend the narrow art-oriented approach, widening the focus of attention to include objects, phenomena and activities of our contemporary world that had been traditionally neglected or forgotten. Challenges to the traditional scope, nowadays aestheticians recognize the continuity between fine arts and experiences from other domains of life. They discuss about the complex circumstances and coexistent ways of life and claim the aesthetic character of different aspects in our everyday life. Thus, aesthetics can not only be considered a subdiscipline of philosophical studies, but an essential study of humanities. In this context, this presentation attempts to defend that John Dewey’s insights into aesthetic experience and its melioristic nature seems to offer fresh insights into the field of current aesthetics. Dewey holds that there is a relation between theory and practice, employing a concept of experience which interprets aesthetics in terms of creativity. He develops a contextualist approach which begins in “the raw”, i.e. in the events and objects that arise in everyday life. Therefore, aesthetic experience does not come about in a finished world, but in one where human beings continuously lose and reestablish harmony with their surroundings.
Keywords: Estética; Aesthetic; Experience; Meliorism; Pragmatism